“No Viral, No Justice”: State Extractivism, Structural Violence, and the Politics of Visibility in the Ecological Justice Crisis in Papua - Paulus Laratmase (International Journal of Education, Vocational and Social Science, 2026)
Paulus Laratmase. This study examines the dynamics of power relations among the state, corporations, and Indigenous communities in the context of natural resource exploitation in Papua. Drawing upon the frameworks of political ecology and critical communication theory, the paper demonstrates that extractive projects, such as mining, oil palm plantations, and food estate initiatives have systematically produced structural violence against Indigenous peoples. In circumstances where legal mechanisms fail to deliver justice, the media emerges as an arena of struggle through the production of public visibility, encapsulated in the adage “No Viral, No Justice.” This study argues that media-based advocacy must move beyond mere exposure toward an evidence-based approach grounded in structured and verifiable data. Such an approach is necessary to support sustainable advocacy efforts capable of influencing policy transformation and advancing ecological justice in Papua.